LOVE IN THE WILLIAM SHAKESPEARE’S SONNET CXVI - Donny Adiatmana Ginting (The Seall Journal, 2021)
This research is aimed to analyze kinds of love and how to love depicted in the sonnet 116 written by William Shakespeare. Sonnet is a poem that consists of 14 lines. Sonnet 116 is one of the famous sonnet in the English Literature and scholars are interesting to analyze sonnet 116. The author uses the theory of love proposed by Steven Gans (2020). The research is library research, and the technique to analyze the data is content analysis. Based on the analysis, two types of love revealed in the sonnet 116 consist of fatuous love and companionate love. The fatuous has two lines depicted in line 2 until 4 and 5 until 6. The companionate has one line depicted in line 9 until 12. Commitment, forgiveness and intimacy are revealed in the sonnet 116 as the value of the true love in the sonnet 116.